Musashi2 as a novel predictive biomarker for liver metastasis and poor prognosis in colorectal cancer. (18th January 2016) - Zong, Zhen; Zhou, Taicheng; Rao, Liangjun; Jiang, Zhipeng; Li, Yingru; Hou, Zehui; Yang, Bin; Han, Fanghai; Chen, Shuang
Abstract: Aberrant expression of musashi2 (MSI‐2) has been detected in several malignancies. However, its role in the progression of colorectal cancer (CRC) remains unknown. Our study was designed to investigate the expression and prognostic significance of MSI‐2 protein in patients with colorectal cancer. The expression of MSI‐2 was detected in 164 patients' colorectal cancer and control specimens by the tissue microarray technique and immunohistochemical staining. The correlations between MSI‐2 expression and clinicopathological variables including overall survival were analyzed. The prognostic value of liver metastasis is evaluated by logistic regression and receiver operating characteristic (ROC) analysis. MSI‐2 was highly expressed in 32.9% (54/164) of the colorectal cancer. Overexpression of MSI‐2 was associated with depth of invasion, lymph node metastasis, distant metastasis, liver metastasis, Tumor Node Metastasis (TNM) clinical stage, and Carcinoembryonicantigen (CEA) level ( P = 0.040, 0.014, <0.001, <0.001, 0.003, and 0.002, respectively). In the Cox multivariate test, MSI‐2 overexpression, lymph node metastasis, and distant metastasis were found to be the independent prognostic factors ( P = 0.027, 0.010, and 0.001, respectively). Further logistic regression suggested that TNM stage and MSI‐2 high expression were related to liver metastasis in colorectal cancer patients. Conclusively, our study indicates that MSI‐2 overexpression is associated with an unfavorable prognosis and may be a potential biomarker for liver metastasis in colorectal cancer patients. Abstract : Our study indicates that MSI‐2 overexpression is associated with an unfavorable prognosis and may be a potential biomarker for liver metastasis in colorectal cancer patients.